Cyber-physical attacks : a growing invisible threat - Loukas, George (Oxford : Butterworth-Heinemann is an imprint of Elsevier, 2015)
Cyber-Physical Attacks: A Growing Invisible Threat presents the growing list of harmful uses of computers and their ability to disable cameras, turn off a building's lights, make a car veer off the road, or a drone land in enemy hands. In essence, it details the ways cyber-physical attacks are replacing physical attacks in crime, warfare, and terrorism. The book explores how attacks using computers affect the physical world in ways that were previously only possible through physical means. Perpetrators can now cause damage without the same risk, and without the political, social, or moral outrage that would follow a more overt physical attack. Readers will learn about all aspects of this brave new world of cyber-physical attacks, along with tactics on how to defend against them. The book provides an accessible introduction to the variety of cyber-physical attacks that have already been employed or are likely to be employed in the near future.
GPS Spoofing/MeaconingMalware Infection; Man-in-the-Middle; Network Isolation; Packet Sniffing; Password Cracking; Relay Attack; Replay Attack; Rogue Node; Sleep Deprivation; Supply Chain Attack; Antiforensics; Summary; Follow-Up Questions and Exercises; 6 Protection Mechanisms and Secure Design Principles; Protection Mechanisms; Authentication; Access Control; Firewall; Intrusion Detection; Antimalware; Application Whitelisting; Flow Whitelisting; Cryptography; Integrity Verification; Survivability; Secure Design Principles; Economy of Mechanism; Defense-in-Depth; Least-Privilege
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed May 27, 2015).
Elsevier
Keywords: Cyber intelligence (Computer security); Ubiquitous computing; Embedded computer systems; Embedded Internet devices; Internet of things; COMPUTERS / Internet Security; COMPUTERS / Networking / Security; COMPUTERS / Security / General; Cyber intelligence (Computer security); Embedded computer systems; Embedded Internet devices; Internet of things; Ubiquitous computing; Electronic books; Electronic books